Data Storage Scheme Supporting for Multidimensional Query - Keji Mao; Xiaomin Zhao; Qike Shao; Wenxiu He; Yanqiang Ou; Qingzhang Chen (International Journal of Distributed Sensor Networks)
The query and storage of data is very important in wireless sensor networks (WSN). It is mainly used to solve how to effectively manage the distributed data in the monitored area with extremely limited resources. Recent advances in technology have made the number of the sensing modules in one sensor develop from single to multiple. The existing storage scheme for one-dimensional data is not suitable for the multidimensional data or costs too much energy. We proposed a kind of data storage scheme supporting multidimensional query inspired by K-D tree. The scheme can effectively store the high-dimensional similar data to the same piece of two-dimensional area. It can quickly fix the storage area of the event by analyzing the query condition and then fetch back the query result. Meanwhile the scheme has a certain degree of robustness to packet loss and node failure. Finally the experiment on the platform of Matlab showed that our scheme has some advantages compared with the existing methods.